Exercise Training for Heart Failure Patients with and without Systolic Dysfunction: An Evidence-Based Analysis of How Patients Benefit - Neil Smart (Cardiology Research and Practice)
Significant benefits can be derived by heart failure patients from exercise training. This paper provides an evidence-based assessment of expected clinical benefits of exercise training for heart failure patients. Meta-analyses and randomized, controlled trials of exercise training in heart failure patients were reviewed from a search of PubMed, Cochrane Controlled Trial Registry (CCTR), CINAHL, and EMBASE. Exercise training improves functional capacity, quality of life, hospitalization, and systolic and diastolic function in heart failure patients. Heart failure patients with preserved systolic function (HFnEF) participating in exercise training studies are more likely to be women and are 5–7 years older than their systolic heart failure (CHF) counterparts. All patients exhibit low functional capacities, although in HFnEF patients this may be age related, therefore subtle differences in exercise prescriptions are required. Published works report that exercise training is beneficial for heart failure patients with and without systolic dysfunction.